Information and communication technology for fisheries industry development in Malaysia - Omar, Siti Zobidah; Abu Hassan, Musa; Mohamed Shaffril, Hayrol Azril; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva (Academic Journals, 2011)
There is a considerable relationship between information and communication technology (ICT), community and industry development. Abundance of previous research have tried to investigate ICT benefits for groups such as farmers, rural community, urban community, students, teacher and businessmen but yet there has been very little research on the roles of ICT can play for the development of the fisheries industry and the fishermen. Based on this problem statement, this paper aim to fulfill the three objectives determined which are to 1) to identify the most preferred ICT among the fishermen; 2) to identify the problems and obstacles faced by the fishermen in using ICT and 3) to determine the benefits that ICT can offer to the fishermen. This is a qualitative study; data was gained through four in-depth interviews guided by an interview guide with responsible agencies officers and fishermen. The questions served as a guide, but allowed respondents freedom and flexibility in their answers. ICT in this paper refer to global positioning system (GPS), sonar, wireless set, computer, internet and mobile phone. Based on the results gained, it can be concluded that GPS is the most preferred ICT among the fishermen. Among problems that need to be overcome to further encourage ICT usage among the fishermen are the negative attitude towards ICT usage, expensive cost, still depends on the traditional way, no exposure on ICT usage and ICT benefits, and no need for them to use the computer and the internet and increasing age. Based on the analyses done, it can be concluded that ICT offers a lot of benefits such as increasing socio-economic level of the fishermen, increase fishermen knowledge and skills on ICT, ease the communication process and enhance the safety aspects of the fishermen when they are on the sea. Based on the results gained it is recommended that the number of ICT seminar, workshop and course given to the fishermen should be doubled with the older fishermen should be included as one of the target groups while ICT subsidy for the fishermen can be given to the fishermen who need it.